Mayoral Leadership in Shaping Urban Beautification in Surabaya and Aspects Influencing Its Capacity - Faruq Ibnul Haqi; Sri Tuntung Pandangwati (EMARA: Indonesian Journal of Architecture, 2020)
Leadership has an expansive meaning because it is a field study that comprises several different dimensions such as psychology, management, organization, and politics. On the other hand, the study of leadership’s role on urban development issues is still relatively scarce, especially in developing countries. The literature shows that local governments under the mayor as the highest-ranking position of municipal prioritise urban development is very much a function of socio-cultural norms and leadership styles. Therefore, mayoral leadership is vital regarding local government interventions to promote urban beautification in Indonesia. It is undeniable that leadership is a significant aspect of urban governance. Taking a case study in Surabaya, evidence shows that leadership plays important roles in urban governance, especially in facilitating and advising processes. Drawing on analysis of relevant documents, literature, and interviews with key decision-makers in Surabaya, the findings indicate that the quality of mayoral leadership has played a vital role in enhancing the beautification of urban form in Surabaya as a result of the urban design process. The mechanisms underlying this role include that the mayor has a sound understanding of the urban design and has been able to intervene to insist on good urban design as policy and has the standing to approach officials and community members on the urban beautification process. The quality of mayoral leadership has played a vital role in shaping the better urban beautification of Surabaya. A Mayor who has a wide-ranging grasp of urban design has advantages for the local government.